Prediction of tropical cyclones by numerical models A review - PRASAD, K. (MAUSAM, 1997)
ABSTRACT. This paper contains a review of some past and recent developments in cyclone track prediction problem by dynamical models. The early attempts aimed at predicting tropical cyclone motion by using simple barotropic models based on vertically integrated vorticity tendency equation. Barotropic models are still used operationally in some centres due to their simplicity. However, current emphasis is on advanced primitive equation models incorporating physical processes, like cumulus convection, which are necessary to account for a major component of the cyclone movement. An important aspect of cyclone prediction by dynamical models is prescription of a correctly analysed synthetic vortex in the initial fields for running a forecast model. Several approaches developed by various groups for generating synthetic vortex are discussed. Examples of some cases of track prediction by limited area model in IMD and by global models are illustrated.